2017
DOI: 10.33369/joall.v2i2.5954
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Argument Structure of Research Article of English Postgraduate Program of Bengkulu University Published In Journal

Abstract: This study investigates the argument pattern in research articles by postgraduate students of English and Education University Bengkulu, based on Toulmin’s Theory (1958). This study analyzed the argument pattern, and reveal the type of data used by the student to support the claim in their argument contains in introduction section and discussion section of Journal Applied Lingusitic and Literature (JOALL) 2016. The data analysis result show that (a) the common argument pattern employed for arguments in introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In addition, there was no pattern in Toulmin's arguments for five elements and six elements. Previous researchers also reported that Toulmin's argument patterns with complete or almost complete elements were rare in writing [49][50][51]. Judging from the existence of the argument element, only the qualifier element was not present in the redox reaction and electrochemistry topic.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, there was no pattern in Toulmin's arguments for five elements and six elements. Previous researchers also reported that Toulmin's argument patterns with complete or almost complete elements were rare in writing [49][50][51]. Judging from the existence of the argument element, only the qualifier element was not present in the redox reaction and electrochemistry topic.…”
Section: Resultsmentioning
confidence: 93%
“…This discourse analysis technique is focusing on analyzing the structure of speeches; rhetoric speeches by model Bottom-Up. The stage analysis by Bermani, Safnil, and Arono (2019) is prior to the discourse analysis, discourse reading, and watching carefully to understand the ideas, then each speech is divided into units (T-units). According to Krippendorff in Bermani, Safnil, Arono (2019), the component of content analysis are coding, classification, and interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…Rebuttal identifies weaknesses in arguments by undermining either the use of a component in the core argument or the content of a component in the core argument (Moon et al, 2016;Admoko et al, 2021a). With the argumentation pattern above, it is expected that students will lead to six components, namely ground, claim, warrant, backing, qualifier, and rebuttal so that the argument is built from complete components and has a good logical structure (Abdollahzadeh et al, 2017;Bermani, 2017). From these complete components and a good structure, students' arguments can be understood easily, and their quality can be measured easily (Chun & Sauder, 2021;Küng & Leimeister, 2021).…”
Section: Introductionmentioning
confidence: 99%